2017
DOI: 10.1016/j.bjm.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Selection, isolation, and identification of fungi for bioherbicide production

Abstract: Production of a bioherbicide for biological control of weeds requires a series of steps, from selection of a suitable microbial strain to final formulation. Thus, this study aimed to select fungi for production of secondary metabolites with herbicidal activity using biological resources of the Brazilian Pampa biome. Phytopathogenic fungi were isolated from infected tissues of weeds in the Pampa biome. A liquid synthetic culture medium was used for production of metabolites. The phytotoxicity of fungal metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Several groups have recently isolated and identified Diaporthe species that have potential for use as microbial bioherbicides. [31][32][33] Bastos et al 34 have shown enhanced efficacy of herbicidal effect of the fermented broths of Diaporthe species by formulation with wileyonlinelibrary.com/journal/ps adjuvants. None of these studies have related the activity of these microbes to the production of specific phytotoxins.…”
Section: N-(tert-butyl)-2-chloro-6-(2-hydroxy-2-methylpropyl)-3-methyl-mentioning
confidence: 99%
“…Several groups have recently isolated and identified Diaporthe species that have potential for use as microbial bioherbicides. [31][32][33] Bastos et al 34 have shown enhanced efficacy of herbicidal effect of the fermented broths of Diaporthe species by formulation with wileyonlinelibrary.com/journal/ps adjuvants. None of these studies have related the activity of these microbes to the production of specific phytotoxins.…”
Section: N-(tert-butyl)-2-chloro-6-(2-hydroxy-2-methylpropyl)-3-methyl-mentioning
confidence: 99%
“…However, these compounds have the potential to provide a competitive advantage for seedling growth through infection and growth retardation of weed seedlings. Therefore, isolation and structural characterization and mode of action of phytotoxins produced by pathogenic fungi for weeds, including aquatic invasive plants, should be investigated [41].…”
Section: Resultsmentioning
confidence: 99%
“…The strain used in this study was Diaporthe sp., previously isolated by Souza et al (2016). The culture was maintained in a potato dextrose agar (PDA) at 4°C and subcultured every 15 days.…”
Section: Microorganism and Inoculummentioning
confidence: 99%
“…has shown interesting results (Souza et al 2015(Souza et al , 2016Pes et al 2016;Briscoe 2014). Species of Diaporthe has been studied for production of molecules with antibacterial (Specian et al 2012), antifungal (Prada et al 2009) and for control of Phyllosticta citricarpa in citrus (Santos et al 2016).…”
Section: Introductionmentioning
confidence: 97%